Understanding the effect of organisational reward on knowledge sharing: the role of exchange ideology and knowledge sharing visibility. (1st January 2013) - Zhang, Xi; Vogel, Doug
The relationship between reward and knowledge sharing is complicated. Although several prior studies explained this relationship from economic perspectives, recent empirical studies find inconsistent results with different behavioural perspectives. One important reason is that most studies examine this relationship in one special organisational environment. This study used cross-sectional data with almost 100 respondents from more than ten organisations in different fields. In this study, we examined the impact of individual value and organisational context on reward-knowledge sharing relationship. The findings support the hypotheses that with cross-sectional data, personal perception of knowledge sharing visibility is the critical factor by contributing the most R square change.